PENGARUH PEMBIAYAAN MUDHARABAH, MURABAHAH, MUSYARAKAH TERHADAP KESEJAHTARAAN UMKM MELALUI LABA - Mubarok, M. Rizky; Faisol, Faisol; Puspita, Erna (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
This research is motivated by the importance of Islamic financing in supporting the growth and welfare of Micro, Small, and Medium Enterprises (MSMEs). Islamic financing schemes such as mudharabah, murabahah, and musyarakah offer alternative financing models based on profit-sharing and partnership, which are considered to be more equitable and capable of fostering sustainable business development. The purpose of this study is to analyze the influence of mudharabah, murabahah, and musyarakah financing on MSME welfare, and to examine the mediating role of profit in this relationship. This study employs a quantitative approach using primary data collected through questionnaires distributed to 100 MSME customers of Bank BTPN Syariah Kediri Branch. The analytical technique used is Structural Equation Modeling (SEM) with the SmartPLS software. The results show that mudharabah, murabahah, and musyarakah financing have a positive direct effect on MSME welfare. However, the indirect effect through profit is not statistically significant. These findings indicate that the improvement in MSME welfare is primarily driven by the direct impact of the financing received. The implications of this research highlight the importance of optimizing Islamic financing that focuses on empowering businesses directly. Islamic banks are expected to enhance literacy and provide ongoing support to MSME actors so that financing funds can be utilized productively to improve business capacity and sustainability.